Physical activity and global genomic DNA methylation in a cancer-free population - Zhang, Fang Fang (Landes Bioscience, 2011)
Changes in DNA methylation may represent an intermediate step between the environment and human diseases. Little is known on whether behavioral risk factors may modify gene expression through DNA methylation. To assess whether DNA methylation is associated with different levels of physical activity, we measured global genomic DNA methylation using bisulfite-converted DNA and real-time PCR (MethyLight) for LINE-1 in peripheral blood of 161 participants aged 45–75 years enrolled in the North Texas Healthy Heart Study and levels of physical activity using an accelerometer (Actigraph GT1M Monitor). We found that individuals with physical activity 26–30 min/day had a significantly higher level of global genomic DNA methylation compared to those with physical activity ≤10 min/day (β = 2.52, 95% CI: 0.70, 4.35). However, the association was attenuated and became statistically insignificant after multivariate adjustment (β = 1.24, 95% CI: −0.93, 3.40). There were some suggestions of a positive association between physical activity and global genomic DNA methylation in non-Hispanics (β = 1.50, 95% CI: −0.08, 3.08) that warrants further investigation.